Taking the Pulse: State of the (He)art of Entrepreneurial Emotion Research. Issue 2 (April 2022) - Javadian, Golshan; Gupta, Alka; Foo, Maw-Der; Batra, Safal; Gupta, Vishal K.
Research on the role of affect in the entrepreneurial process has surged over time, resulting in a vibrant field of inquiry. To advance scholarship in this area, we conduct an inductive analysis of 162 published articles, critically analyzing the state of research on affect in entrepreneurship. We develop an organizing framework to capture three major conversations in existing research—affect valence (feelings), discrete emotions, and emotional competencies—and encompass several outcomes studied within each conversation. We find that limited work has been done to explore the antecedents of affect (both feelings and discrete emotions), anticipated affect deserves greater consideration, and affective influence of stakeholders on entrepreneurs remains overlooked. Research on negative affect and emotional competencies also remains scarce in the entrepreneurship literature. Future inquiry would do well to take a multilevel approach to affect, explore affective phenomena over time, and cast light on the role of emotional competencies in the entrepreneurial process. We also spotlight crucial empirical advancements, including big data and artificial intelligence, for affect research going forward.